Morphofunctional analysis of antigen uptake mechanisms following sublingual immunotherapy with beads in mice - Elewa, Yaser Hosny Ali (PLoS One, 2018)
BACKGROUND: Recently, sublingual immunotherapy (SLIT) has been used as a safe and efficient method for the treatment of and immunization against asthma and various allergies. However, the routes of antigen/allergen (particulate antigen) uptake through the mucosa of the oral cavity remain incompletely understood, as do the roles of sex and age in the process. For this purpose, to elucidate the mechanism and efficacy of SLIT among different sexes and ages, microbeads were dripped into the sublingual region to mimic particulate antigen uptake by the sublingual mucosa. METHODS: Twenty microliters of either phosphate buffered saline (PBS) or fluorescently labelled microbeads (latex and silica beads) were placed under the tongue of both male and female C57BL/6 mice at young (3 months) and old (6 months) ages. The lower jaw was examined 30 min after administration, and beads were detected with a fluorescence stereomicroscope. Morphological observations of the mucosa of the fluorescent areas were made with a scanning electron microscope (SEM) and an all-in-one light fluorescence microscope (LM). Fluorescence intensity was compared between both sexes and ages. RESULTS: Stereomicroscopic observation revealed fluorescent illuminations in three compartments of the sublingual mucosa: the sublingual caruncles (SC), the oral rostral mucosa (OR) and the buccal mucosa (BM). Interestingly, the fluorescence intensity tended to be higher among females than among males in the SC region in particular. However, there were no significant age-related differences. SEM and LM revealed beads in the lumina of both mandibular ducts and sublingual ducts (Sd). Additionally, the apical cytoplasm of some Sd cells contained silica beads. However, there was no specification in the OR mucosa or BM. CONCLUSIONS: This study reveals the major role Sd plays in local immunity via the antigen uptake mechanisms. Furthermore, our data suggest that the efficacy of SLIT in humans could be affected by sex.